Factors Influencing the Knowledge Level of Pap Smear Examination in Cervical Cancer Patients - Wulan M. Soemardji (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To describe the level of knowledge of Pap smear examination and its influencing factors in cervical cancer patients. Methods: Patients meeting the inclusion criteria were asked to fill questionnaire. Acquired data will then be processed and analyzed statistically. Result: This study was performed to 45 cervical cancer patients. We found that the majority of subjects was in the 41-45 years age groups (36%), housewife (87%), graduated junior high school (51%), and lived in Manado city (53.3%). Thirty one patients (69%) had a lacking knowledge about Pap smear examination. Among 25 respondents (56%) who had received the information before, only 13 respondents (52%) had already had their Pap smear examination. This unwillingness to participate in the examination was caused by fear (75%), laziness (8%), no complaint (8%), and no support from the husband (8%). The information factor had the greatest influence on the level of knowledge about Pap smear examination. Conclusion: The knowledge level of Pap smear is still low and the most influencing factor for this result is the lack of information (p < 0.05). [Indones J Obstet Gynecol 2012; 36-2: 61-5] Keywords: cervical cancer patients, information, knowledge, Pap smear